Quest for Identity: what is gained and lost on the way - Komarovskaya, Tatiana (Respectus Philologicus, 2005)
The article is devoted to the investigation of the problem of how the main theme of feminist literature, a woman’s search for identity, for her place in the world, and the consequences of this search, unfolds in the novels of contemporary writers Jane Smiley, Jane Hamilton and Margaret Atwood. J. Smiley, in her novels, maintains that when a woman steps over her feminist fate, she gains only loneliness and a lack of perspective, which brings misfortune upon her children.J. Hamilton analyses a psychological aspect of a woman’s search for identity (the novel “A Map of the World”). M Atwood elaborates upon the political character of the feminist movement and its possible consequences in her dystopia “A Handmaid’s Tale”.Maternal love as one of the significant concepts of feminist prose and its role in the upbringing of daughters is at the base of T. Morrison’s novel “Sula” and M Gordon’s novel “Men and Angels “, and, thus, becomes the focus of the analysis of these two novels in the article. The consideration of the novels goes hand in hand with the examination of the change of gender stereotypes of behaviour peculiar to the novels of feminist writers (Smiley’s “A Thousand Acres”; T. Morrison’s “Sula”).